Induced Pluripotent Stem Cell Potential in Medicine, Specifically Focused on Reproductive Medicine - Botman, Olivier; Wyns, Christine (Frontiers in Surgery, 2014)
Since 2006, several laboratories have proved that somatic cells can be reprogrammed into induced pluripotent stem cells (iPSC). iPSCs have enormous potential in stem cell biology as they can give rise to numerous cell lineages, including the three germ layers. In this review, we discuss past and recent advances in human iPSCs used for modeling diseases in vitro, screening drugs to test new treatments, and autologous cell and tissue regenerative therapies, with a special focus on reproductive medicine applications. While this latter field of research is still in its stage of infancy, it holds great promise for investigating germ cell development and studying the genetic and physiopathological mechanisms of infertility. A major cause of infertility is the absence of germ cells in the testes, mainly due to genetic background or as a consequence of gonadotoxic treatments. For these patients, no effective fertility restoration strategy has so far been identified. The derivation of germ cells from iPSCs represents an alternative source of stem cells able to differentiate into spermatozoa. Lessons learned from animal models as well as studies on human iPSCs for reproductive purposes are reviewed.